The Relationship Between Height, Weight, Body Mass Index and Uric Acid in The Elderly Community - Ninik Nurhidayah; Aniek Puspitosari (Jurnal Penelitian Pendidikan IPA, 2023)
The elderly population continues to increase every year. Efforts to improve the quality of life of the elderly are carried out by the government and society. Empowering the elderly community through posyandu and community associations is useful for improving the health status of the elderly. Every month a health check is carried out, but no research has been carried out regarding the checks carried out. The aim of the research was to determine the relationship between height, weight, body mass index and uric acid levels in the elderly. The research method is a cross-sectional study design. The research was conducted at the Cerbonan Karanganyar elderly community. Data collection was done using purposive sampling. The number of respondents was 51 elderly. Instruments use starter meters, weight scales, auto check tools and uric acid strips. The data analysis technique uses the Pearson correlation technique. The results of the research show that the majority of elderly people are female, 43 (83%). The elderly group aged 60-69 years are the largest community members, 40 (78.4%). There is a positive and significant correlation between height and weight (r=0.443, p=0.001, CI: 0.191-0.640), height and uric acid (r=0.359, p=0.010, CI: 0.093-0.578), height body mass index (r=0.446, p=0.001, CI: 0.194-0.642), body weight with gout (r=0.328, p=0.019, CI: 0.058-0.554), body mass index with gout (r =0.329, p=0.019, CI: 0.058-0.554).